(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
In addition to heredity, the biological and especially technological properties of cocoons are greatly influenced by the conditions of cocoon wrapping - temperature, humidity, light, ventilation (aeration), the quantity and quality of cocoons.As a result of temperature changes during cocoon wrapping, the speed and nature of the silkworm wrapping the silk fibers into the cocoon shell of the worm also change.